Impact of soil application with selenite and selenate on ‘soil-highland barley-dietary’ system in Tibet - Zhou, Chenni; Duan, Fei; Wang, Jiangke (Frontiers in Plant Science, 2025)
IntroductionSelenium (Se)-fortified foods have demonstrated efficacy in augmenting dietary Se intake and ameliorating human Se nutritional status. To mitigate Se deficiency-related health risks in Tibetan populations, systematic biofortification trials targeting highland barley, the primary staple crop in Tibet, are imperative.MethodsHighland barley was subjected to soil-applied selenate (SeVI) and selenite (SeIV) at seven rates (0, 5, 15, 25, 50, 75, and 100 g·ha-1), followed by comprehensive evaluation of Se transfer dynamics within the soil-crop-diet continuum across Tibet’s agricultural regions.Results and discussionExogenous Se application significantly increased the Se content in highland barley grains (p < 0.05), with SeVI proving to be more effective than SeIV. Selenomethionine (SeMet) accounted for 78-85% of total Se species in grains, and SeIV applications yielding 1.7 times higher organic Se conversion rates compared to SeVI treatments. Se application not only elevated the total Se concentration but also concurrently increased the bioavailable Se fractions in the soil, thereby enhancing Se translocation within the plant. Dietary exposure assessment indicated that application rates of 75 g·ha-1 SeIV and 50 g·ha-1SeVI were optimal, as they satisfied the recommended daily intake (55 μg·day-1) for Tibetan adults while keeping soil Se below 3.0 mg·kg-1. This study demonstrated that soil application of 75 g·ha-1 SeIV or 50 g·ha-1 SeIV achieved effective biofortification without ecological risk, providing a sustainable solution for mitigating Se deficiency in Tibetan agroecosystems.